Dispersion of short period surface waves and the surficial Layer in the region west of Delhi (MAUSAM, 1969)
Short period surface waves with periods between 5and 20 seconds recorded at Delhi due to earth-quakes in West Pakistan have been studied. Dispersion of both Rayleigh and Love waves obtained from the study has been compared with theoretical single layer models and it is inferred that the sediments overlying the granitic basement over the wave paths are about 5-km.